PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA BIMA - Mukhlis; AmirulMukminin; Wahdatun Aulia (Jurnal Nusa Manajemen, 2024)
This research aims to determine the influence of work motivation and work discipline on the performance of Bima City Transportation Department employees. The approach used in the research is an associative approach. The population in the study was 188 employees with a sample of 32 ASN employees. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test which were processed using the Statistical Product and Service Solution (SPSS) version 20 program. that Work Motivation (X1) and Work Discipline (X2) simultaneously have a significant effect on the Performance of Bima City Transportation Service Employees.